The frequency of analgesic drug use and causes in 65 years old and above; A family medicine unit experience. - Öksüz, Ahmet; Atadağ, Yıldız; Aydın, Abdülkadir; Kaya, Didem (Journal of Surgery and Medicine, 2017)
Aim: The elderly population in Turkey is increasing. One of the most common health problems among the elderly population, which increases day by day, is pain. The use of analgesics due to pain is seen at very high levels and the use of analgesics in the prescription is increasing. In this study, we aimed to determine the frequency and causes of drug use among elderly patients who applied to our unit of family medicine and used regular pain relievers. Methods: Our study was done by retrospectively scanning the files of 65 years old and over individuals who applied for Sivas Ulas Family Health Centre for any reason. The number of patients aged 65 years and over registered to the family health centre is 286. 43 individuals who regularly used NSAID were included in the study. Results: Forty-three patients (15%) who used regular analgesic medication were present in our polyclinic admission for any reason. Participants were using analgesic medication due to diffuse muscle and skeletal pain in 48.8% (n=21), gonarthrosis in 48.8% (n=21) and arthritis in 2.3% (n=1). The analgesic drug was using 32.6% (n=14) frequently paracetamol. Conclusion: As a result, the use of analgesics is as commonplace in our country as it is in the world. Drug use should be monitored regularly, especially in elderly patients, as serious side effects associated with analgesic use may occur.